(untitled) (Journal of the College of Basic Education, 2022)
The study aimed to reveal the degree of effect of addition of the internet and social networking sites on changing the secondary school students’ social values in Mosul. The study adopted the descriptive approach; the study sample contained (483) male and female secondary school students in Nineveh District. The sample was stratified random selected from the study population. A questionnaire was used as the study instrument. The average degree of the effect of addition of internet and social networking sites on changing the secondary school students’ social values was (3.42), which is a large degree. The factor of communication had the highest degree of effect among the social values ​​factors; it represented an average of (3.46); a large degree. The communication domain followed by the factor of customs and traditions, which represented an average of (3.43); a large degree. The factor of ethics and religion came the last and represented an average of (3.38); a medium degree. The study also showed that the degree of the effect of internet and social networking sites addiction on males outweighs females. There was no difference in the degree of effect of internet and social networking sites addiction due to specialization.